Natural convection in semi trapezoidal enclosure - Abd. Aziz, Mohamad Redhwan (2006)
Numerical analysis approach for natural convection in semi trapezoidal shaped cavity is investigated by applying constant heat flux from the top. Buoyancy consideration of Boussinesq approximation noted valid for this incompressible problem of ideal gas with low (Pr) Prandtl number (Pr=0.7) and laminar steady state condition. Taking a physical geometry of semi trapezoidal enclosure with aspect ratio of 1.5, with top wall been constantly applied heat flux (constant heat flux boundary condition) while inclined sidewall is been kept at same temperature (isothermal boundary condition). Bottom and vertical side wall are been insulated and assumed z-direction to be infinite (2 - dimensional). The integral forms of the governing equations are solved by control volume based finite volume method using SIMPLE algorithm. Parametric study on the behavior of the isotherms and velocity profiles in the cavity would then be elaborated upon the final results.